Low-dimensional materials for alkaline oxygen evolution electrocatalysis. (March 2019) - Kong, Xiangkai; Peng, Zhenmeng
Abstract: The urge for renewable and clean energy technologies has cultivated the concept of hydrogen economy, in which water electrolysis for hydrogen production is one indispensable component. As the water electrolysis efficiency is primarily restricted by the anodic oxygen evolution reaction (OER), intensive research efforts have been put into this field to acquire good knowledge of the reaction mechanism and obtain active, durable, and cost-effective electrocatalyst materials. Many invaluable findings have been achieved in the past years, with some problems being found in the meantime. It is good timing to summarize what have been achieved and identify what to overcome, which would be helpful to unscramble current OER research status and stimulate insightful thoughts in future studies. In this review article, we briefly introduce current understanding of OER electrocatalysis mechanism and the use of catalyst descriptor parameters for correlation with the activity property. We then summarize recent achievements on development of OER catalyst materials, which are categorized and discussed based on their morphological dimension. Perspectives on the existing challenges and future directions in the OER research are also provided. Highlights: Current understanding of oxygen evolution reaction (OER) electrocatalysis mechanism is surveyed. Recent achievements on low-dimensional OER catalyst development are summarized. Perspectives on future directions in the OER research are provided.